Lychees and mirrors: local opera, cinema and diaspora in the Chinese cultural cold war - Taylor, Jeremy E. (Johns Hopkins University Press, 2018)
This paper explores the fate of a southern Fujianese opera (liyuanxi) play that was reformed over the course of the early 1950s and eventually made into the first full-length film to be produced in southern Fujianese dialect (Minnanyu) in the People's Republic of China. It does this, however, in order to shed light on much wider battles that raged, from the mid-1950s to the early 1960s, over control of a plethora of local and provincial performance arts on both sides of the Taiwan Strait and between pro- and anti-Communist community groups throughout the Chinese diaspora in Southeast Asia. The story of this one particular play-cum-film―Chen San Wuniang (Chen San and “Fifth Daughter”; 1957)―highlights that it was often rapidly shifting Cold War geopolitics, rather than ideological content or quality, that determined the outcome of such battles.